Xbox One - Roese, Neal J.; Meagher, Evan ([London] : SAGE, 2016)
When the Xbox One console was officially revealed, Microsoft effectively confirmed that it would require an always-on connection for validating digital rights. Predictably, gamers reacted negatively, a response that was exacerbated when Microsoft's president of the interactive entertainment business, Don Mattrick, made dismissive statements about their concerns. This study examines how Microsoft dealt with the situation.
Originally Published in: Roese, N. J., & Meagher, E. (2014). Xbox One. 5-114-006. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Microsoft Corporation; Xbox one (Video game console); Marketing -- Case studies